Penerapan Metode Pembelajaran Realistic Mathematics Education (RME) untuk Meningkatkan Hasil Belajar Pemusatan Data Tunggal - M. Zaenal Muttaqin (Journal on Education, 2022)
This study aims to determine whether nor not there is an increase in Single Data Centering learning outcomes through the application of Realistic Mathematics Education (RME) learning methods in 6-E grade students of SD Negeri Wonokusumo VI/45 Surabaya. The low learning outcomes of Single Data Centering are also experienced by students of grade 6-E SD Negeri Wonokusumo VI/45 Surabaya requiring handling in terms of the teaching and learning process carried out. Authors as their Class Teachers are responsible for finding solutions to improve Single Data Centering learning outcomes. The perspective taken is to increase student activity in the teaching and learning process. This is related to the selection of learning models, therefore innovation in the application of learning models and methods must be carried out through the application of Realistic Mathematics Education (RME) learning methods. The application of this learning method involves seven main components of productive learning, namely: constructivism (Constructivism), asking (Questioning), finding (Inquiry), learning community (Learning Community), modeling (Modelling), reflection (Reflection) and actual assessment (Authentic). Assessment) The research was conducted with a two-cycle action mechanism. And based on the results of the analysis, it can be concluded that there is an increase in learning outcomes of Single Data Centering through the application of Realistic Mathematics Education (RME) learning methods in grade 6-E students of SDN Wonokusumo VI/45 Surabaya. Realistic Mathematics Education (RME) learning in 6-E grade students of SDN Wonokusumo VI/45 Surabaya is an average of 23%.